Clinical Characteristics and Predictive Factors of Invasive Fungal Disease in Pediatric Oncology Patients with Febrile Neutropenia in a Country with Limited Resources - Monsereenusorn C; Sricharoen T; Rujkijyanont P; Suwanpakdee D; Photia A; Lertvivatpong N; Traivaree C (Dove Medical Press, 2021)
Chalinee Monsereenusorn,1 Thitiyaporn Sricharoen,2 Piya Rujkijyanont,1 Detchvijitr Suwanpakdee,3 Apichat Photia,1 Nawachai Lertvivatpong,1 Chanchai Traivaree1 1Division of Hematology/Oncology, Department of Pediatrics, Phramongkutklao Hospital and Phramongkutklao College of Medicine, Bangkok, Thailand; 2Buayai Hospital, Nakhon Ratchasima, Thailand; 3Division of Infectious Disease, Department of Pediatrics, Phramongkutklao Hospital and Phramongkutklao College of Medicine, Bangkok, ThailandCorrespondence: Chalinee MonsereenusornDivision of Hematology/Oncology, Department of Pediatrics, Phramongkutklao Hospital and Phramongkutklao College of Medicine, 315 Ratchawithi Road, Ratchathewi, Bangkok, 10400, ThailandEmail chalinee_monsereenusorn@pedpmk.orgBackground: The most common complication among pediatric oncology patients is febrile neutropenia (FN). Invasive fungal disease (IFD) is suspected when fever persists > 4- 7 days after empirical antibiotics. Its clinical characteristics and predictive factors associated with IFD among pediatric oncology patients with FN were thus explored.Methods: Pediatric oncology patients with FN between January 1, 2012 and December 31, 2016 were enrolled in this study. Clinical characteristics, including laboratory investigations, treatment modalities, and final outcomes of IFD were retrospectively reviewed and analyzed.Results: In all, 73 patients with 180 episodes of confirmed diagnosis of FN were studied. Median age at diagnosis was 6.2 years, with equal sex distribution. The most common diagnosis was acute lymphoblastic leukemia (n=91, 51%), followed by acute myeloid leukemia (n=47, 26%), Burkitt's lymphoma (n=7, 4%) and neuroblastoma (n=7, 4%). Median absolute neutrophil count at FN diagnosis was 0 (0- 806) cells/mm3. IFD was diagnosed for 25 (14%) episodes. Mortality rates for FN and IFD were 4% and 20%, respectively. Respiratory compromise, oxygen requirement, hypotension, prolonged hospitalization, duration of fever and neutropenia, bacteremia, bacteriuria, funguria, abnormal liver-function results, and prolonged broad-spectrum antibiotic administration were factors associated with IFD (P< 0.05). Prolonged duration between initiation of fever and antifungal administration for nearly 10 days was an independent factor in prediction of IFD occurrence (P= 0.014).Conclusion: Respiratory compromise, oxygen requirement, hypotension, prolonged hospitalization, duration of fever and neutropenia, bacteremia, bacteriuria, funguria, abnormal liver-function results and prolonged broad-spectrum antibiotic administration were factors associated with IFD. Duration between initiation of fever and antifungal administration of nearly 10 days were considered a risk factors of IFD among patients with FN.IRB Reference Number: IRBRTA 825/2560.Keywords: febrile neutropenia, invasive fungal disease, pediatric oncology, risk factors, mortality